2019
DOI: 10.15414/jmbfs.2019/20.9.3.516-520
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic Properties and Antioxidant Efficiency of Lactobacillus Plantarum 15 Isolated From Milk

Abstract: Many researchers are focusing on the investigation of new molecules and substances to help the body fighting oxidative stress; among them are probiotic bacteria. In this study we investigated the probiotic properties and the antioxidative activity of Lactobacillus plantarum 15 isolated from milk. Therefore, to evaluate probiotic potential of the selected strain, the antibacterial activity and resistance to acidic pH and bile salts conditions were evaluated. Moreover, several methods were used to analyze the an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Since oxidative stress antagonistically influences the occurrence of inflammation, cellular damage, and disease susceptibility in the body (56,57), the postbiotic produced by L. plantarum has the potential to reduce the oxidation of proteins and lipids particularly through two mechanisms, namely, HRS and RP. Unlike other previous studies that reported on the DPPH and ABTS activities of L. plantarum (27,58), two other assays were used in the current research to elucidate further the antioxidant activity of postbiotic produced by L. plantarum. HRS measured the scavenging activity of the most reactive radical, hydroxyl radical, which is related to lipid peroxidation and biomolecules of cells (59).…”
Section: Antioxidant Activity Of L Plantarum Postbioticsmentioning
confidence: 99%
“…Since oxidative stress antagonistically influences the occurrence of inflammation, cellular damage, and disease susceptibility in the body (56,57), the postbiotic produced by L. plantarum has the potential to reduce the oxidation of proteins and lipids particularly through two mechanisms, namely, HRS and RP. Unlike other previous studies that reported on the DPPH and ABTS activities of L. plantarum (27,58), two other assays were used in the current research to elucidate further the antioxidant activity of postbiotic produced by L. plantarum. HRS measured the scavenging activity of the most reactive radical, hydroxyl radical, which is related to lipid peroxidation and biomolecules of cells (59).…”
Section: Antioxidant Activity Of L Plantarum Postbioticsmentioning
confidence: 99%
“…Additionally, previous research highlighted the superior free radical scavenging activities of supernatants from various LAB strains ( L. plantarum , L. paracasei , E. faecium, L. helveticus, W. paramesenteroides, and P. pentosaceus ) compared to the control strain L. rhamnosus GG [ 32 ]. Another study conducted demonstrated that the probiotic strain L. plantarum 15 exhibited a DPPH scavenging activity of 75.21% and displayed different levels of reducing power (FRAP) [ 59 ]. Similarly, Han et al [ 60 ] demonstrated that the CFS of L. acidophilus , L. plantarum , L. curvatus, L. sake , P. pentosaceus , and L. fermentum isolated from Harbin dry sausages possessed reducing activities exceeding 1.4 Mm.…”
Section: Resultsmentioning
confidence: 99%
“…This helps to regulate the immune system and lower serum cholesterol levels. Improves the equilibrium of intestinal microorganisms to promote human health ( 16 ). Certain strains of lactic acid bacteria (LAB) have been observed to elevate the concentrations of pro-inflammatory markers such as TNF-α, IL-1β, and IL-6 while concurrently reducing the expression of anti-inflammatory markers (Arg 1, TGF-β, and CD206).…”
Section: Introductionmentioning
confidence: 99%